Ameaças e perspectivas de conservação do Tubarão-Cabeça-Chata na Região Metropolitana do Recife - Rossetto, Lucas Medeiros Pereira Barata (Universidade Federal de São Carlos, 2025)
The present study aimed to analyze and compile information on the anthropogenic impacts affecting the population of bull sharks in the Metropolitan Region of Recife (RMR-PE), seeking to understand how urbanization, habitat degradation, and fishing activities influence this species. A literature review was conducted to support this analysis. The RMR has undergone intense transformation driven by accelerated urbanization, industrialization, and unplanned land occupation, factors that have led to the loss and fragmentation of coastal and estuarine habitats essential for the bull shark (Carcharhinus leucas), an euryhaline apex predator that uses these environments as breeding, nursery, and foraging grounds. Anthropogenic pressures on the species are multiple and cumulative, including physical and hydrological alterations associated with urban and industrial expansion—such as mangrove suppression and the construction works at the Port of Suape—chronic pollution resulting from deficient sanitation and the discharge of domestic and industrial effluents, as well as emerging stressors like noise and light pollution that affect the species’ orientation and behavior. Fishing pressure, especially through accidental capture (bycatch) and the reduction of natural prey, combined with habitat degradation, forces C. leucas into urbanized coastal areas where organic waste disposal may attract individuals and increase negative interactions with humans. These impacts are further intensified by climate change, which alters temperature and salinity and imposes additional stressors that influence migratory patterns. Overall, the bull shark emerges as a sentinel species for the vulnerability of Pernambuco’s coastal ecosystems, reinforcing the urgent need for integrated conservation strategies that prioritize sanitation, effluent control, mangrove restoration, and selective fisheries management.
Threats and conservation prospects for Bull Sharks in the Metropolitan Region of Recife (RMR-PE)
Keywords: Carcharhinus leucas; Ecossistemas costeiros pernambucanos; Pressões antrópicas; Porto de Suape; Coastal ecosystems of Pernambuco; Anthropogenic pressures; Port of Suape; CIENCIAS BIOLOGICAS::ECOLOGIA; 14. Vida na Água